A remark on the r-th mean differentiability - George D. Stamatelos (International Journal of Mathematics and Mathematical Sciences)
This paper is concerned with the r-th mean differentiability. In the mathematical developments regarding the asymptotic expansion and the asymptotic distribution of the likelihood function, there arises the question whether the assumptions made on the model imply differentiability in the r′-th mean of the underlying random functions, for integer values r′<r. The present paper provides an answer to this question and also gives the explicit form of the derivatives in the r′-th mean involved.